2015
DOI: 10.1111/jir.12192
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitive training in adolescents with chromosome 22q11.2 deletion syndrome: feasibility and preliminary effects of the intervention

Abstract: Background Children with chromosome 22q11.2 deletion syndrome (22q11DS) often have deficits in social cognition and social skills that contribute to poor adaptive functioning. These deficits may be of relevance to the later occurrence of serious psychiatric illnesses such as schizophrenia. Yet, there are no evidence-based interventions to improve social cognitive functioning in children with 22q11DS. Methods Using a customised social cognitive curriculum, we conducted a pilot small-group-based social cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…Intervention models for targeted psychosocial training in 22q11.2DS have already been proposed [79, 80] and cognitive enhancement therapy of tailored exercises, which include perspective taking and identification of non-verbal social clues, has been shown to improve social cognitive abilities in adolescents with 22q11.2DS [80]. Also, the training scheme applied by Glaser et al [79] which targets focusing on the eyes, emotion recognition and understanding, and working memory has shown short-term improvements in these functions.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention models for targeted psychosocial training in 22q11.2DS have already been proposed [79, 80] and cognitive enhancement therapy of tailored exercises, which include perspective taking and identification of non-verbal social clues, has been shown to improve social cognitive abilities in adolescents with 22q11.2DS [80]. Also, the training scheme applied by Glaser et al [79] which targets focusing on the eyes, emotion recognition and understanding, and working memory has shown short-term improvements in these functions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is possible that the types of social concerns endorsed on the SRS (e.g., eye contact, odd behaviors, preference for being alone, ritualistic behaviors) may not relate as closely as we originally hypothesized to the TASIT's measurement of nuanced social cognition skills such as lie and sarcasm detection. have previously been proposed, with one pilot study that found targeted training in the identification of nonverbal social cues and perspective taking is associated with significant gains in social cognitive abilities in adolescents with 22q11DS (70). Adapting existing treatment models from idiopathic ASD and psychosis to better suit the cognitive needs of individuals with 22q11DS could improve social cognition, and thereby overall quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous studies in idiopathic psychosis (93) and ASD (94) suggests that psychosocial and social skills training show positive treatment effects for both groups even 3-4 months post-treatment on average, suggesting good generalizability of social skills treatment gains, and improved overall functioning and sense of well-being. Intervention models directed at improving psychosocial function in individuals with 22q11DS have previously been proposed, with one pilot study that found targeted training in the identi cation of nonverbal social cues and perspective taking is associated with signi cant gains in social cognitive abilities in adolescents with 22q11DS (95). Adapting existing treatment models from idiopathic ASD and psychosis to better suit the cognitive needs of individuals with 22q11DS could improve social cognition, and thereby overall quality of life.…”
Section: Discussionmentioning
confidence: 99%